Respiratory Severity Score as a Predictive Factor for the Mortality of Congenital Diaphragmatic Hernia - Ja-Hye Ahn; Young Hwa Jung; Seung Han Shin; Hyun-Young Kim; Ee-Kyung Kim; Han-Suk Kim (Korean Society of Neonatology, 2018)
Purpose Congenital diaphragmatic hernia (CDH) is rare but potentially fatal. The overall outcome is highly variable. This study aimed to identify a simple and dynamic parameter that helps predict the mortality of CDH patients in real time, without invasive tests. Methods We conducted a retrospective chart review of 59 CDH cases. Maternal and fetal information included the gestational age at diagnosis, site of defect, presence of liver herniation, and lung-to-head ratio (LHR) at 20 to 29 weeks of gestational age. Information regarding postnatal treatment, including the number of days until surgery, the need for inhaled nitric oxide (iNO), the need for extracorporeal membrane oxygenation (ECMO), and survival, was collected. The highest respiratory severity score (RSS) within 24 hours after birth was also calculated. Results Statistical analysis showed that a younger gestational age at the initial diagnosis (P<0.001), a lower LHR (P=0.001), and the presence of liver herniation (P= 0.003) were prenatal risk factors for CDH mortality. The RSS and use of iNO and ECMO were significant factors affecting survival. In the multivariate analysis, the only remaining significant risk factor was the highest preoperative RSS within 24 hours after birth (P=0.002). The area under the receiver operating characteristic curve was 0.9375, with a sensitivity of 91.67% and specificity of 83.87% at the RSS cut-off value of 5.2. The positive and negative predictive values were 82.14% and 92.86%, respectively. Conclusion Using the RSS as a prognostic predictor with simple calculations will help clinicians plan CDH management.